High strength aluminum alloy for 3D printing and its manufacturing method
The Al-Mg-Zr-Si-based high-strength aluminum alloy for 3D printing addresses the challenge of achieving simultaneous strength and stretching ratio by optimizing the composition and processing conditions, resulting in enhanced yield strength and productivity.
Patent Information
- Application Number
- JP2023568282
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-05-04
- Filing Date
- 2022-05-03
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2042-05-03
AI Technical Summary
Existing methods for manufacturing Al-Mg aluminum alloys struggle to simultaneously achieve sufficient strength and stretching ratio, due to difficulties in harmonizing the types and amounts of elements added, leading to variations in productivity and quality.
The development of an Al-Mg-Zr-Si-based high-strength aluminum alloy for 3D printing, with a composition of magnesium (Mg) 2-13, silicon (Si) 1-5, and zirconium (Zr) 0.5-1.5 in weight %, along with the remainder being aluminum (Al) and inevitable impurities, to satisfy the relation 1.5≦[Mg]/[Si]≦8.5, which enhances yield strength and productivity.
This alloy achieves a yield strength of 400 MPa or more and a stretching ratio of 7% or more, while maintaining productivity and quality, by optimizing the composition and processing conditions for 3D printing.
Smart Images

Figure 0007662832000005 
Figure 0007662832000006 
Figure 0007662832000001
Abstract
Description
[Technical Field]
[0001] The present invention relates to a high-strength Al-Mg-Zr-Si-based aluminum alloy for 3D printing, which consists of, by weight, 2 to 13 magnesium (Mg), 1 to 5 silicon (Si), 0.5 to 1.5 zirconium (Zr), and the remainder aluminum (Al), and a method for producing the same. [Background technology]
[0002] Metal 3D printing is a processing method based on AM (additive manufacturing), which uses CAD (computer-aided design) models to easily produce products with complex shapes that cannot be realized with existing manufacturing technologies.
[0003] Metal 3D printing has the advantage of shortening the time required for product development compared to traditional processing techniques such as casing, forging, welding, and extruding.
[0004] Due to these advantages, various prior patents, such as Korean Patent No. 10-1754523 and Korean Patent No. 10-1145124, have disclosed methods for manufacturing metal products using metal 3D printing technology, and related technologies have been published in numerous papers, including in the Journal of the Korean Society for Laser Processing.
[0005] However, it has been difficult to determine the composition of an Al-Mg based aluminum alloy that can simultaneously secure sufficient strength and elongation, and there are significant differences in productivity and quality depending on the type and amount of added elements, making it difficult to appropriately balance these. Summary of the Invention [Problem to be solved by the invention]
[0006] In order to solve the above-mentioned problems, the present invention aims to provide an Al-Mg-Zr-Si high-strength aluminum alloy for 3D printing, which is composed of, by weight, 2 to 13 magnesium (Mg), 1 to 5 silicon (Si), 0.5 to 1.5 zirconium (Zr), and the balance aluminum (Al), ensuring yield strength and productivity. [Means for solving the problem]
[0007] In order to achieve the above object, one embodiment of the present invention relates to an Al-Mg-XY-based aluminum alloy for 3D printing, characterized in that in the Al-Mg-XY-based aluminum alloy, X reacts with the aluminum (Al) to form an Al-X intermetallic compound, and Y reacts with the magnesium (Mg) to form an Mg-Y intermetallic compound.
[0008] According to one embodiment, the X is any one element selected from zirconium (Zr), titanium (Ti), scandium (Cs), hafnium (Hf), and yttrium (Y), and the Y is silicon (Si). 、 It may be any one element selected from tin (Sn), zinc (Zn), and germanium (Ge).
[0009] According to one embodiment, it is possible to provide an Al-Mg-Zr-Si based high-strength aluminum alloy for 3D printing, which contains, by weight %, 2 to 13 magnesium (Mg), 1 to 5 silicon (Si), and 0.5 to 1.5 zirconium (Zr), with the remainder consisting of aluminum (Al) and unavoidable impurities, and the weight % of the magnesium (Mg) and the silicon (Si) satisfy the following relational expression 1: [Equation 1] 1.5≦[Mg] / [Si]≦8.5 (In the above Relational Formula 1, [Mg] means the weight % of magnesium (Mg), and [Si] means the weight % of silicon (Si).)
[0010] According to the embodiment, the Al-Mg-Zr-Si based high strength aluminum alloy for 3D printing may contain 5 to 10 wt % of magnesium (Mg).
[0011] According to one embodiment, the Al-Mg-Zr-Si based high-strength aluminum alloy for 3D printing may further include 0.01 to 0.2 wt % of calcium (Ca). According to one embodiment, the Al-Mg-Zr-Si based high-strength aluminum alloy for 3D printing may be provided in powder form or wire form.
[0012] According to another embodiment of the present invention, there is provided an Al-Mg-Zr-Si-based high-strength aluminum alloy product manufactured by 3D printing, characterized in that the Al-Mg-Zr-Si-based high-strength aluminum alloy contains, by weight, 2 to 13 magnesium (Mg), 1 to 5 silicon (Si), and 0.5 to 1.5 zirconium (Zr), with the remainder consisting of aluminum (Al) and unavoidable impurities, and the weight percentages of the magnesium (Mg) and silicon (Si) satisfy the following relational expression 1: [Equation 1] 1.5≦[Mg] / [Si]≦8.5 (In the above Relational Formula 1, [Mg] means the weight % of magnesium (Mg), and [Si] means the weight % of silicon (Si).) According to the embodiment, the high-strength aluminum alloy product may have a yield strength of 400 to 500 MPa. According to the embodiment, the Al-Mg-Zr-Si high-strength aluminum alloy may contain 5 to 10 wt % of magnesium (Mg). According to the embodiment, the elongation of the high-strength aluminum alloy product may be 7% or more.
[0013] According to another embodiment of the present invention, there is provided a method for producing an Al-Mg-Zr-Si-based high-strength aluminum alloy product using 3D printing, the method comprising the steps of: (a) preparing an Al-Mg-Zr-Si-based aluminum alloy powder or aluminum alloy wire containing, by weight, 2-13 magnesium (Mg), 1-5 silicon (Si), and 0.5-1.5 zirconium (Zr), with the remainder being aluminum (Al) and unavoidable impurities, wherein the weight percentages of the magnesium (Mg) and the silicon (Si) satisfy the following relational expression 1; and (b) 3D printing the Al-Mg-Zr-Si-based aluminum alloy powder to produce a product. [Equation 1] 1.5≦[Mg] / [Si]≦8.5 (In the above Relational Formula 1, [Mg] means the weight % of magnesium (Mg), and [Si] means the weight % of silicon (Si).)
[0014] According to the embodiment, the Al-Mg-Zr-Si based aluminum alloy powder or aluminum alloy wire may contain 5 to 10 wt % of magnesium (Mg).
[0015] According to one embodiment, the Al-Mg-Zr-Si based aluminum alloy powder or aluminum alloy wire is ,mosquito It may further contain 0.01 to 0.2 wt % of calcium (Ca). [Effects of the Invention]
[0016] According to the method for producing an Al-Mg-Zr-Si-based high-strength aluminum alloy for 3D printing of the present invention, by limiting the composition of the aluminum alloy to, by weight %, 2 to 13 magnesium (Mg), 1 to 5 silicon (Si), 0.5 to 1.5 zirconium (Zr), and the remainder aluminum (Al-based) and unavoidable impurities, it is possible to provide an aluminum alloy product for 3D printing having a yield strength of 400 MPa or more. [Brief explanation of the drawings]
[0017] [Figure 1] 1 is a flowchart illustrating a method for manufacturing a high-strength Al-Mg-Zr-Si-based aluminum alloy for 3D printing according to an embodiment of the present invention. [Figure 2] 1 is a graph illustrating the correlation between beam velocity and ultimate tensile strength depending on the silicon content when the laser power is fixed at 170 W. DETAILED DESCRIPTION OF THE INVENTION
[0018] Hereinafter, the Al-Mg-Zr-Si-based high-strength aluminum alloy for 3D printing and a manufacturing method thereof according to the present invention will be described in detail. The drawings introduced below are provided as examples to fully convey the concept of the present invention to those skilled in the art. Therefore, the present invention is not limited to the drawings presented below and may be embodied in other forms, and the drawings presented below may be exaggerated to clarify the concept of the present invention. In this regard, unless otherwise defined, the technical and scientific terms used have the meanings commonly understood by those skilled in the art to which the present invention belongs. In the following description and the accompanying drawings, descriptions of well-known functions and configurations that may unnecessarily obscure the gist of the present invention will be omitted.
[0019] Generally, in Al-Mg based aluminum alloys, the types and amounts of additional elements added are adjusted to ensure desired physical properties such as strength and elongation. In this process, it is difficult to simultaneously ensure appropriate strength and elongation, and significant differences in productivity and quality occur depending on the types and amounts of added elements, making it difficult to achieve a proper balance.
[0020] One embodiment of the present invention is an Al-Mg based high strength aluminum alloy for 3D printing, more preferably teeth, This relates to an Al-Mg-XY-based aluminum alloy in which two or more elements are contained in an Al-Mg-based aluminum alloy.
[0021] In this specification, X and Y refer to elements contained in the Al-Mg based aluminum alloy. Specifically, X refers to an element in the Al-Mg based aluminum alloy that forms an intermetallic compound with aluminum (Al), and Y refers to an element in the Al-Mg based aluminum alloy that forms an intermetallic compound with magnesium (Mg).
[0022] According to the embodiment, the mechanical properties of the Al-Mg-XY-based aluminum alloy can be controlled by designing the composition of X or Y within an appropriate range. For example, when the composition of X in the Al-Mg-XY-based aluminum alloy increases, hot cracking, which is a common phenomenon in Al-Mg for 3D printing, can be prevented and strength can be improved. In particular, melting caused by absorbing laser energy during 3D printing and rapid cooling (10 6 ° C. / sec), the X can exist in a supersaturated state in the Al-Mg-XY-based aluminum alloy.
[0023] Subsequently, X precipitates internally during heat treatment, significantly improving the strength of the Al-Mg-XY-based aluminum alloy. However, if X is excessively contained in the Al-Mg-XY-based aluminum alloy, some X may become unsaturated and exist in the form of segregation. This can significantly reduce the elongation rate of the aluminum alloy and increase its brittleness.
[0024] The Y element in the Al-Mg-XY-based aluminum alloy does not react with aluminum (Al) but reacts with magnesium (Mg). Specifically, the Y element forms an intermetallic compound with magnesium (Mg) to prevent hot cracking during high-speed forming, thereby improving the quality of 3D printed products and improving the strength of the Al-Mg-XY-based aluminum alloy. Like X, the Y element precipitates within the Al-Mg-XY-based aluminum alloy, significantly improving its strength. Furthermore, excessive Y content in the Al-Mg-XY-based aluminum alloy can significantly reduce the elongation rate and increase its brittleness.
[0025] According to the embodiment, the X may react with the aluminum (Al) to form an Al-X intermetallic compound, and the Y may react with the magnesium (Mg) to form an Mg-Y intermetallic compound. In addition, the fractions of the Al-X intermetallic compound and the Mg-Y intermetallic compound in the Al-Mg-XY-based aluminum alloy and the microstructure of the alloy may be changed depending on the 3D printing process conditions (e.g., laser power, beam speed, laser beam diameter, laser beam scan pattern, build plate temperature during the 3D printing process, and heat treatment conditions after 3D printing output), thereby allowing users to control the physical properties, quality, and productivity of their products.
[0026] According to the embodiment, the X is any one element selected from zirconium (Zr), titanium (Ti), scandium (Sc), hafnium (Hf) and yttrium (Y), and the Y is silicon (Si). 、 It is characterized by being any one element selected from tin (Sn), zinc (Zn) and germanium (Ge), but is not limited thereto, and it is obvious that it can be transformed into a predetermined component that can react with the aluminum (Al) or magnesium (Mg). Hereinafter, in this specification, zirconium (Zr) will be exemplified as the X element, and silicon (Si) as the Y element.
[0027] Therefore, the present invention provides an Al-Mg-based aluminum alloy with silicon (Si) and zirconium (Zr), and the alloy composition contains, by weight, 2 to 13 magnesium (Mg), 1 to 5 silicon (Si), and 0.5 to 1.5 zirconium (Zr), with the remainder consisting of aluminum (Al) and unavoidable impurities, and is capable of producing an aluminum alloy product produced by 3D printing that ultimately has a yield strength (YS) of 400 MPa or more, as well as a method for producing the same.
[0028] According to another embodiment of the present invention, the Al-Mg-Zr-Si based high-strength aluminum alloy for 3D printing further contains 0.01 to 0.2 wt % of calcium (Ca), thereby suppressing oxidation and vaporization of magnesium (Mg) during the manufacturing process of the alloy, thereby improving productivity.
[0029] In the manufacturing process of ordinary Al-Mg based aluminum alloys, oxidation of magnesium (Mg) progresses, resulting in the formation of large amounts of oxides such as MgO, Al2O3, and Al2MgO4, which can cause various defects in the metal.
[0030] To prevent this, the present invention allows calcium (Ca) to be added in an amount of 0.01 to 0.2 wt % to an Al-Mg aluminum alloy, preferably an Al-Mg-Zr-Si aluminum alloy. The calcium (Ca) reacts with magnesium (Mg) contained in the aluminum alloy to form a (Mg,Ca)O2 film, thereby preventing oxidation of the magnesium (Mg).
[0031] Furthermore, during 3D printing, conventional Al-Mg-based aluminum alloys can lose some of their magnesium (Mg) due to vaporization caused by the melt pool generated by the laser beam. During this process, some of the magnesium vaporizes and floats in the air, generating fumes. These fumes can scatter the laser beam during laser scanning by the 3D printer, adversely affecting 3D printing productivity and product quality. To prevent this, the present invention adds calcium (Ca) to increase the ignition temperature of magnesium (Mg).
[0032] That is, calcium (Ca) increases the ignition temperature of magnesium (Mg), thereby preventing excessive fume generation at the melting point and reducing the loss of magnesium (Mg) due to vaporization in the melt pool, thereby improving productivity.
[0033] The composition ranges of Al-Mg-Zr-Si-based high-strength aluminum alloys for 3D printing according to embodiments of the present invention will be described in detail below. Unless otherwise specified, the units are in weight percent.
[0034] According to one embodiment, the Al-Mg-Zr-Si based high-strength aluminum alloy for 3D printing may contain, by weight percent, 2-13 magnesium (Mg), 1-5 silicon (Si), and 0.5-1.5 zirconium (Zr), with the remainder being aluminum (Al) and unavoidable impurities. Magnesium (Mg) is contained in an amount of 2 to 13% by weight.
[0035] Magnesium (Mg) plays a role in determining the strength of the Al-Mg-Zr-Si based high-strength aluminum alloy. Specifically, magnesium (Mg) can precipitate the Mg2Si phase with silicon (Si) in the alloy, thereby achieving a precipitation strengthening effect. For this reason, to ensure the strength of the Al-Mg-Zr-Si based high-strength aluminum alloy, it is preferable that magnesium (Mg) be included in an amount of 2 wt% or more. If magnesium (Mg) is included in an amount less than 2 wt%, it is difficult to ensure sufficient strength.
[0036] On the other hand, if the magnesium (Mg) content exceeds 13 wt%, excessive fumes are generated during the 3D printing process, making it difficult to output or manufacture a good product. This is because the fumes generated by the evaporation of some of the magnesium (Mg) can scatter the laser beam. For this reason, the magnesium (Mg) content may be provided in a range of 2 to 13 wt%, preferably 5 to 10 wt%, and more preferably 5 to 7 wt%. Silicon (Si) is contained in an amount of 1 to 5% by weight.
[0037] As mentioned above, silicon (Si) can react with magnesium (Mg) to precipitate the highly hard Mg2Si phase. This induces precipitation hardening in the Al-Mg-Zr-Si high-strength aluminum alloy, significantly improving its strength. If the silicon (Si) content is less than 1 wt%, hot cracking may occur during high-speed 3D printing of the Al-Mg-Zr-Si high-strength aluminum alloy, resulting in reduced quality of the 3D printed product.
[0038] According to the embodiment, the silicon (Si) may be contained in an amount of 1 wt% or more to ensure sufficient strength of the aluminum alloy, but if the silicon content exceeds 5 wt%, the proportion of Mg2Si phase becomes too high, which is an advantage as it reduces the elongation ratio.
[0039] On the other hand, in the Al-Mg-Zr-Si based high strength aluminum alloy, the silicon (Si) and the magnesium (Mg) can satisfy the following relational expression 1. [Equation 1] 1.5≦[Mg] / [Si]≦8.5 (In the above Relational Formula 1, [Mg] means the weight % of magnesium (Mg), and [Si] means the weight % of silicon (Si).)
[0040] If the weight percent ratio of magnesium (Mg) to silicon (Si) in the Al-Mg-Zr-Si-based high-strength aluminum alloy is less than 1.5, the amount of magnesium (Mg) relative to silicon (Si) may be insufficient, resulting in a reduced degree of Mg2Si phase precipitation, resulting in a negligible improvement in strength. Furthermore, during 3D printing, a decrease in the silicon weight ratio can increase the energy required during 3D printing, significantly impacting productivity. The productivity-reducing effect of silicon (Si) will be described in more detail with reference to Figure 2 below.
[0041] On the other hand, if the weight percent ratio of the magnesium (Mg) to the silicon (Si) in the Al-Mg-Zr-Si high-strength aluminum alloy is 8.5 or more, the silicon (Si) content will be relatively reduced, and the Mg2Si phase may not precipitate sufficiently. For this reason, the weight percent ratio of the magnesium (Mg) to the silicon (Si) in the Al-Mg-Zr-Si high-strength aluminum alloy may be 1.5 to 8.5, and more preferably 1.5 to 7.0. Zirconium (Zr) is contained in an amount of 0.5 to 1.5 wt %.
[0042] Zirconium (Zr) contributes to grain refinement in conventional aluminum (Al) alloys, thereby suppressing hot cracking during 3D printing of Al-Mg-based aluminum alloys. Furthermore, zirconium (Zr) can react with aluminum (Al) to form the Al3Zr phase. That is, zirconium (Zr) can improve the elongation strength of Al-Mg-Zr-Si-based high-strength aluminum alloys by refining the grains, and simultaneously strengthen the strength by precipitating the Al3Zr phase. To achieve these effects, zirconium (Zr) is preferably added in an amount of 0.5 wt% or more.
[0043] However, if the Zr content exceeds 1.5 wt%, the melting temperature of the Al-Mg-Zr-Si high-strength aluminum alloy may increase, resulting in increased loss of magnesium (Mg) due to vaporization. Furthermore, some of the zirconium (Zr) may become unsaturated and precipitate through segregation. This significantly reduces the elongation rate of the Al-Mg-Zr-Si high-strength aluminum alloy, increasing its brittleness and ultimately reducing the quality of the 3D printing product. For these reasons, the Zr content is preferably 0.5 to 1.5 wt%. Calcium (Ca) is contained in an amount of 0.2% by weight or less.
[0044] As described above, the calcium (Ca) can prevent the oxidation of the magnesium (Mg), and the magnesium (Mg) M( Mg) to increase the ignition temperature, thereby suppressing the generation of fumes.
[0045] The calcium (Ca) may be selectively included depending on the magnesium (Mg) content in the alloy. For example, if the magnesium (Mg) content in the Al-Mg-Zr-Si high-strength aluminum alloy is 5 wt % or less, the magnesium (Mg) may be oxidized and have only a slight effect on the aluminum alloy, so calcium (Ca) may not be included.
[0046] However, if the magnesium (Mg) content in the Al-Mg-Zr-Si high-strength aluminum alloy exceeds 5 wt%, the magnesium (Mg) may be oxidized, which may affect the strength and productivity of the Al-Mg-Zr-Si high-strength aluminum alloy. In this case, the calcium (Ca) may be included in a variable amount depending on the magnesium (Mg), and preferably, the weight ratio of the magnesium (Mg) to the calcium (Ca) may be 1:0.8 to 1:1.2.
[0047] If the weight ratio of magnesium (Mg) to calcium (Ca) is less than 1:0.8, calcium (Ca) is contained in a relatively small amount compared to magnesium (Mg), and productivity may decrease due to oxidation and vaporization of magnesium (Mg). If the weight ratio of magnesium (Mg) to calcium (Ca) is more than 1:1.2, calcium (Ca) acts as an impurity in the Al-Mg-Zr-Si based high-strength aluminum alloy, and the strength of the aluminum alloy may decrease.
[0048] For these reasons, in the Al-Mg-Zr-Si high-strength aluminum alloy, the weight ratio of the magnesium (Mg) to the calcium (Ca) is preferably 1:0.8 to 1:1.2.
[0049] According to the embodiment, the Al-Mg-Zr-Si based high strength aluminum alloy may have a shape such as, but not limited to, pieces, powder, or wires.
[0050] The composition of the Al-Mg-Zr-Si-based high-strength aluminum alloy for 3D printing according to the embodiment of the present invention has been described above. Below, a method for manufacturing the Al-Mg-Zr-Si-based high-strength aluminum alloy for 3D printing according to the embodiment of the present invention will be described. FIG. 1 is a flowchart illustrating a method for manufacturing a high-strength Al-Mg-Zr-Si-based aluminum alloy for 3D printing according to an embodiment of the present invention.
[0051] 1, a method for manufacturing an Al-Mg-Zr-Si-based high-strength aluminum alloy for 3D printing according to an embodiment of the present invention may include the steps of (a) preparing an Al-Mg-Zr-Si-based aluminum alloy powder or aluminum alloy wire containing, by weight, 2-13 magnesium (Mg), 1-5 silicon (Si), and 0.5-1.5 zirconium (Zr), with the remainder being aluminum (Al) and unavoidable impurities, wherein the weight percentages of the magnesium (Mg) and silicon (Si) satisfy the following relational expression 1, and (b) 3D printing the Al-Mg-Zr-Si-based aluminum alloy powder to manufacture a product. In this case, the weight percentages of the magnesium (Mg) and silicon (Si) in the Al-Mg-Zr-Si-based aluminum alloy powder or aluminum alloy wire may satisfy the following relational expression 1. [Equation 1] 1.5≦[Mg] / [Si]≦8.5 (In the above Relational Formula 1, [Mg] means the weight % of magnesium (Mg), and [Si] means the weight % of silicon (Si).)
[0052] In step (a), aluminum alloy powder can be produced by using a method such as gas atomizing or extrusion after drawing of the aluminum alloy having the above-mentioned composition.
[0053] First, a molten alloy containing the above-described mother metal or mother alloy is melted to produce a molten alloy, and then an aluminum alloy ingot is produced from the molten alloy. For this melting, a vacuum or atmospheric induction melting furnace or an electric resistance furnace can be used.
[0054] Then, aluminum alloy powder can be produced using methods such as gas atomizing or extrusion after drawing. Since the melting and powder production processes were performed using known methods, detailed description of the processes will be omitted.
[0055] In step (b), the aluminum alloy powder produced in step (a) can be 3D printed to manufacture a desired product. Here, 3D printing can refer to a powder bed fusion (PBF) method in which metal powder is melted and sintered using a laser. Specifically, the powder sintering method (PBF) refers to a method of manufacturing a product by stacking the aluminum alloy powder produced in the above steps and irradiating the stacked powder with an energy laser beam to melt and bond the aluminum alloy powder.
[0056] According to an embodiment, step (b) uses a powder bed fusion (PBF) method, and the spacing between lines (hatch spacing) can be 50 to 1,000 μm and the thickness can be 10 to 100 μm depending on the type of laser, output, or diameter of the laser beam. This method can also be applied to 3D printing processes using a direct energy deposition (DED) method that supplies powder or wire, as well as other conventional binder jet 3D metal printing processes.
[0057] Meanwhile, an Al-Mg-Zr-Si based high strength aluminum alloy product manufactured according to one embodiment of the present invention contains, by weight, 2-13 magnesium (Mg), 1-5 silicon (Si), and 0.5-1.5 zirconium (Zr), with the balance being aluminum (Al) and unavoidable impurities, and the weight percentages of the magnesium (Mg) and silicon (Si) can satisfy the following relational expression 1: [Equation 1] 1.5≦[Mg] / [Si]≦8.5 (In the above Relational Formula 1, [Mg] means the weight % of magnesium (Mg), and [Si] means the weight % of silicon (Si).) An explanation of the above relational expression 1 will be omitted.
[0058] According to the examples, the Al-Mg-Zr-Si high-strength aluminum alloy product manufactured by the above-mentioned composition and manufacturing method can have a yield strength of 400 to 500 MPa and an elongation of 2.7% or more.
[0059] The Al-Mg-Zr-Si-based high-strength aluminum alloy for 3D printing and a manufacturing method thereof according to the present invention will be described in more detail below with reference to the following examples. However, the following examples are merely a reference for explaining the present invention in detail, and the present invention is not limited thereto and can be realized in various forms.
[0060] Furthermore, unless otherwise defined, all technical and scientific terms have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. The terms used in the description of this specification are for the purpose of effectively describing specific examples and are not intended to limit the present invention. Furthermore, the unit of additives not specifically described in the specification may be weight percent.
[0061] A. Comparison of yield strength by chemical composition Metal raw materials were prepared according to the compositions shown in Table 1 below, and the metal raw materials were melted and then gas atomized to produce Al-Mg-Zr-Si based high strength aluminum alloy powder.
[0062] The produced aluminum alloy powder was output using a 3D printing method using the Powder Bed Fusion (PBF) method. The metal 3D printer used was a dpert M135 manufactured by DAEGUNTECH. Using the metal 3D printer, a 170W laser was scanned onto the aluminum alloy powder to produce laminated aluminum alloy test pieces with a layer thickness of 30μm and a hatch spacing of 150μm.
[0063] [Table 1]
[0064] In Examples 1 to 7 and Comparative Examples 1 to 7, the Al-Mg-Zr-Si high-strength aluminum alloys for 3D printing were processed to a gauge length of 10 mm and a diameter of 4 mm to prepare tensile test specimens.
[0065] The surfaces of the prepared test specimens were machined, and tensile tests were performed at room temperature according to ASTM E8 Standard Test Methods for Tension Testing of Metallic Materials. The measured yield strength and elongation are shown in Table 2 below.
[0066] [Table 2]
[0067] Referring to Table 2, it can be seen that the Al-Mg-Zr-Si high-strength aluminum alloys for 3D printing manufactured in Examples 1 to 7 all have a yield strength of 400 MPa or more.
[0068] In contrast, Comparative Example 1, which does not contain zirconium (Zr), has a yield strength of 3 6The yield strength was 8.1 MPa and the elongation was 8%, which was a decrease of 85.9 MPa and 3% compared to Example 2, which had the same composition but contained 1.2 wt % zirconium.
[0069] This is because, as mentioned above, the effects of grain refinement and the formation of the Al3Zr phase are not realized due to the absence of zirconium (Zr), and as a result, both the yield strength and elongation of Comparative Example 1 are reduced compared to Example 2.
[0070] Comparative Example 2, which contained 0 wt% silicon (Si), had a yield strength of 309.2 MPa and an elongation rate of 17.6%, which was found to be a decrease of 114.2 to 129.4 MPa in yield strength compared to Examples 5 and 6, which had similar compositions except for the silicon (Si).
[0071] This is because the Mg2Si phase was not formed in Comparative Example 2 due to the absence of silicon (Si), resulting in a relative increase in the fraction of the Al3Zr phase. That is, the increase in the Al3Zr phase improved the elongation, but the absence of the Mg2Si phase resulted in a decrease in strength. This confirms that Comparative Example 2 had a lower yield strength than Examples 5 and 6.
[0072] Comparative Example 3, in which the weight ratio of magnesium (Mg) to silicon (Si) is 1.25, and Comparative Example 4, in which the weight ratio of magnesium (Mg) to silicon (Si) is 15, have yield strengths of 320 MPa and 310 MPa, respectively. In contrast, Examples 1 to 7, in which the weight ratio of magnesium (Mg) to silicon (Si) is 1.5 to 8.5, have yield strengths of 400 MPa. End This is because the magnesium (Mg) and silicon (Si) are not contained properly, and therefore the appropriate amount of Mg2Si phase is not precipitated. Specifically, in Comparative Example 3, the Mg2Si phase is excessively formed, which significantly reduces the elongation rate and causes the yield point. yield pointMany test pieces broke before the test. In Comparative Example 4, the yield strength was reduced due to a lack of the Mg2Si phase. For this reason, it is preferable that the weight percentages of magnesium (Mg) and silicon (Si) are contained within a range that satisfies the following relational expression 1. [Equation 1] 1.5≦[Mg] / [Si]≦8.5 (In the above Relational Formula 1, [Mg] means the weight % of magnesium (Mg), and [Si] means the weight % of silicon (Si).)
[0073] In particular, Example 1, in which the weight percentages of magnesium (Mg) and silicon (Si) satisfy the relational expression 1, and the magnesium (Mg) is contained in an amount of 5 to 7 weight percent, and It can be confirmed that No. 3 has a yield strength of 460 MPa or more and an elongation rate of 7.8% or more. This confirms that the magnesium (Mg) content of 5 to 7 wt % within the range that satisfies the relational expression 1 is a composition that can simultaneously ensure both yield strength and elongation rate.
[0074] In addition, in Comparative Example 4, excessive fumes were generated during the manufacturing process due to the excessive magnesium (Mg). This process was confirmed to cause laser scattering, resulting in a deterioration in the quality of the tensile test specimen. For these reasons, the magnesium (Mg) content is preferably 2 to 13 wt %, and more preferably 5 to 7 wt %, within the range satisfying Relational Formula 1.
[0075] It can be seen that Comparative Example 5 containing 0.3 wt % zirconium (Zr) had a yield strength reduced by 79 MPa compared to Example 2 containing 1.2 wt % zirconium with the same composition.
[0076] This is because, as mentioned above, the zirconium (Zr) content was less than 0.5 wt %, and the degree of strengthening by the Al3Zr phase was very small, resulting in a decrease in yield strength in Comparative Example 5 compared to Example 2.
[0077] Comparative Example 6, which contained 0.5 wt% silicon (Si), and Comparative Example 7, which contained 7 wt% silicon (Si), had yield strengths of 381 MPa and 280 MPa, respectively, indicating a decrease in yield strength compared to Example 2, which contained 2 wt% silicon (Si), and Example 3, which contained 4 wt% silicon (Si) with the same composition. Furthermore, Comparative Example 7 showed a sharp decrease in elongation to 0.2%.
[0078] This is because, as mentioned above, in Comparative Example 6, the silicon (Si) content was less than 1 wt %, and the precipitation strengthening effect of the Mg2Si phase was not fully realized, and in Comparative Example 7, the silicon (Si) content exceeded 5 wt %, and the proportion of the Mg2Si phase was so high that brittleness increased and the elongation rate dropped sharply. In fact, the tensile test specimen manufactured according to Comparative Example 7 had a yield point of 1.5 mm. yield point It has been confirmed that it breaks before.
[0079] B. Comparison of productivity by component composition FIG. 2 is a graph illustrating the correlation between beam velocity and ultimate tensile strength depending on the silicon content when the laser power is fixed at 170 W. Generally, in 3D printing, if the laser power, hatch spacing (= beam scanning interval, hatching space), and layer thickness are fixed, the laser beam speed and the output speed of the product are proportional. In other words, if the above conditions are fixed, the beam speed Increase in This means an increase in the output speed of the product. By checking whether the appropriate yield strength is maintained in this state, productivity can be compared.
[0080] For this reason, aluminum alloy test pieces (Examples 8, 9, and Comparative Example 8) having the compositions shown in Table 3 below, as well as the above-mentioned Examples 1, 2, and 3 and Comparative Example 2, were further prepared.
[0081] [Table 3]
[0082] Then, for aluminum alloy test pieces manufactured with the composition shown in Table 3, the laser power was fixed at 170 W, the 3D printing layer thickness was fixed at 30 μm, and the hatch spacing was fixed at 150 μm. When the beam speed was changed from 200 to 450 mm / s, the ultimate tensile strength (UTS) measurement values are shown in Table 4 below. When the beam speed was changed from 200 to 600 mm / s for some test pieces, the ultimate tensile strength (UTS) measurement values are shown in Figure 2.
[0083] [Table 4]
[0084] Referring to Table 4, Examples 1 to 3 and Example 8, in which 5 to 7 wt % of magnesium (Mg) and 1 to 5 wt % of silicon (Si) were added, maintained an ultimate tensile strength (UTS) of 450 MPa or more, preferably 450 to 550 MPa, at a beam velocity in the range of 200 to 450 mm / sec.
[0085] In contrast, in Comparative Examples 2 and 8, which contained less than 1 wt% silicon (Si), the ultimate tensile strength (UTS) dropped sharply to 400 MPa or less at beam velocities of 300 mm / s or more, and no test specimens were formed at beam velocities of 350 mm / s or more. In fact, when the beam velocity increased to 350 mm / s or more, 3D printing of the test specimens that did not contain silicon (Si) was impossible due to hot cracking.
[0086] That is, it was confirmed that there is a limit to improving productivity when the silicon (Si) content is less than 1 wt %. Specifically, it was confirmed that the productivity of Examples 1 to 3 and Example 8, in which 1 to 5 wt % of silicon (Si) was added, increased by about two times or more compared to Comparative Examples 2 and 8, in which the silicon (Si) content was less than 1 wt %.
[0087] On the other hand, Example 9, which contains 8 wt% magnesium (Mg) and 1 wt% silicon (Si), was confirmed to be able to produce an aluminum alloy through 3D printing even when the beam velocity was 200-450 mm / s. However, since the silicon (Si) content of Example 9 was relatively low compared to the magnesium (Mg), it was confirmed that the ultimate tensile strength (UTS) rapidly decreased when the beam velocity exceeded 350 mm / s. This means that Example 9 requires a certain level of beam velocity to ensure sufficient strength, which means that productivity may be reduced compared to the previous examples.
[0088] 2, it can be seen that the ultimate tensile strength (UTS) decreases to 400 MPa or less when the beam velocity is 350 to 450 mm / s, and then decreases again when the beam velocity exceeds 500 mm / s. In fact, it can be seen that the ultimate tensile strength (UTS) of the test piece manufactured in Example 9 is about 0.6 times lower than that of Examples 1 to 3 and Example 8, which contain 2 to 4 wt% silicon (Si).
[0089] From Example 9, it can be confirmed that in order to maintain the productivity of Al-Mg-Zr-Si based high-strength aluminum alloy products using the 3D printing, in other words, when the laser output is fixed at 170 W, it is more preferable that the weight percentages of the magnesium (Mg) and silicon (Si) satisfy the following relational expression 2: [Equation 2] 1.5≦[Mg] / [Si]≦7.0 (In the above Relational Formula 1, [Mg] means the weight % of magnesium (Mg), and [Si] means the weight % of silicon (Si).)
[0090] As described above, the Al-Mg-Zr-Si-based high-strength aluminum alloy for 3D printing according to the embodiment of the present invention can contain, by weight, 2 to 13 magnesium (Mg), 1 to 5 silicon (Si), and 0.5 to 1.5 zirconium (Zr), with the remainder being aluminum (Al-based) and unavoidable impurities.
[0091] In addition, in order to manufacture an Al-Mg-Zr-Si based high-strength aluminum alloy product using 3D printing, the composition may be configured so that the weight percentages of the magnesium (Mg) and silicon (Si) satisfy the following relational expression 1. [Equation 1] 1.5≦[Mg] / [Si]≦8.5 (In the above Relational Formula 1, [Mg] means the weight % of magnesium (Mg), and [Si] means the weight % of silicon (Si).)
[0092] More preferably, in order to ensure a certain level of productivity for Al-Mg-Zr-Si-based high-strength aluminum alloy products using the 3D printing, in other words, to maintain an ultimate tensile strength (UTS) of 450 MPa or more at a beam speed in the range of 200 to 450 mm / sec, it is more preferable that the weight percentages of the magnesium (Mg) and silicon (Si) satisfy the following relational expression 2. [Equation 2] 1.5≦[Mg] / [Si]≦7.0 (In the above Relational Formula 1, [Mg] means the weight % of magnesium (Mg), and [Si] means the weight % of silicon (Si).)
[0093] Finally, in order to produce an aluminum alloy product having a yield strength of 450 MPa or more and an elongation of 7% or more while simultaneously satisfying the above-mentioned relations 1 and 2, the weight percent of magnesium (Mg) is preferably 5 to 7 weight percent.
[0094] Although the present invention has been described above using specific matters and limited examples, these are provided merely to facilitate a more general understanding of the present invention, and the present invention is not limited to the above examples. Those skilled in the art will appreciate that various modifications and variations can be made from such descriptions.
[0095] Therefore, the spirit of the present invention should not be limited to the described embodiments, and all things that are equivalent to or have equivalent modifications within the scope of the claims, as well as the scope of the claims, should be considered to fall within the scope of the spirit of the present invention.
Claims
1. An Al-Mg-Zr-Si high-strength aluminum alloy for 3D printing comprising, by mass%, 2 to 13 magnesium (Mg), 1 to 5 silicon (Si), and 0.5 to 1.5 zirconium (Zr), with the remainder being aluminum (Al) and unavoidable impurities, wherein the mass percentages of the magnesium (Mg) and silicon (Si) satisfy the following relational expression 1: [Relationship 1] 1.5≦[Mg] / [Si]≦8.5 (In the above Relational Formula 1, [Mg] means the mass % of magnesium (Mg), and [Si] means the mass % of silicon (Si).)
2. The Al-Mg-Zr-Si high-strength aluminum alloy for 3D printing according to claim 1, characterized in that the magnesium (Mg) is contained in an amount of 5 to 10 mass%.
3. The Al-Mg-Zr-Si high-strength aluminum alloy for 3D printing according to claim 1, further comprising 0.01 to 0.2 mass% calcium (Ca).
4. The Al-Mg-Zr-Si high-strength aluminum alloy for 3D printing according to claim 1, characterized in that the Al-Mg-Zr-Si high-strength aluminum alloy for 3D printing has a powder or wire form.
5. An Al-Mg-Zr-Si high strength aluminum alloy product, The Al-Mg-Zr-Si high-strength aluminum alloy contains, by mass%, 2 to 13 magnesium (Mg), 1 to 5 silicon (Si), and 0.5 to 1.5 zirconium (Zr), with the balance being aluminum (Al) and unavoidable impurities; The mass percentages of the magnesium (Mg) and silicon (Si) satisfy the following relational expression 1. [Relationship 1] 1.5≦[Mg] / [Si]≦8.5 (In the above Relational Formula 1, [Mg] means the mass % of magnesium (Mg), and [Si] means the mass % of silicon (Si).)
6. The Al-Mg-Zr-Si high strength aluminum alloy product according to claim 5, characterized in that the yield strength of the high strength aluminum alloy product is 400-500 MPa.
7. The Al-Mg-Zr-Si high-strength aluminum alloy product according to claim 5, characterized in that the Al-Mg-Zr-Si high-strength aluminum alloy contains 5 to 10 mass% of magnesium (Mg).
8. 6. The Al-Mg-Zr-Si high strength aluminum alloy product according to claim 5, wherein the elongation of the high strength aluminum alloy product is 7% or more.
9. (a) preparing an Al-Mg-Zr-Si-based aluminum alloy powder or aluminum alloy wire containing, by mass%, 2 to 13 magnesium (Mg), 1 to 5 silicon (Si), and 0.5 to 1.5 zirconium (Zr), with the remainder being aluminum (Al) and unavoidable impurities, wherein the mass% of the magnesium (Mg) and the silicon (Si) satisfy the following relational expression 1; (b) 3D printing the Al-Mg-Zr-Si-based aluminum alloy powder to produce a product. [Relationship 1] 1.5≦[Mg] / [Si]≦8.5 (In the above Relational Formula 1, [Mg] means the mass % of magnesium (Mg), and [Si] means the mass % of silicon (Si).)
10. The method for producing an Al-Mg-Zr-Si based high strength aluminum alloy product using 3D printing according to claim 9, characterized in that the Al-Mg-Zr-Si based aluminum alloy powder or aluminum alloy wire contains 5 to 10 mass% of magnesium (Mg).
11. The method for producing an Al-Mg-Zr-Si based high strength aluminum alloy product using 3D printing according to claim 9, wherein the Al-Mg-Zr-Si based aluminum alloy powder or aluminum alloy wire further contains 0.01 to 0.2 mass% of calcium (Ca).
Citation Information
Patent Citations
Reinforced aluminum matrix composite and preparation method thereof
CN109692964A
Manufacture of superplastic aluminum alloy
JP1985238459A
Aluminum alloy for cylinder of photoengraving roll for gravure
JP1986272341A
Aluminum alloy for magnetic disk excellent in grindability
JP1992272150A
Connection terminal
JP2004197170A